Repeated H2O2 exposure drives cell cycle progression in an in vitro model of ulcerative colitis. Issue 12 (9th October 2013) - Poehlmann, Angela; Reissig, Kathrin; Schönfeld, Peter; Walluscheck, Diana; Schinlauer, Antje; Hartig, Roland; Lessel, Wiebke; Guenther, Thomas; Silver, Andrew; Roessner, Albert
Abstract The production of hydrogen peroxide (H2O2) drives tumourigenesis in ulcerative colitis (UC). Recently, we showed that H2O2 activates DNA damage checkpoints in human colonic epithelial cells (HCEC) through c‐Jun N‐terminal Kinases (JNK) that induces p21WAF1. Moreover, caspases circumvented the G1/S and intra‐S checkpoints, and cells accumulated in G2/M. The latter observation raised the question of whether repeated H2O2 exposures alter JNK activation, thereby promoting a direct passage of cells from G2/M arrest to driven cell cycle progression. Here, we report that increased proliferation of repeatedly H2O2‐exposed HCEC cells (C‐cell cultures) was associated with (i) increased phospho‐p46 JNK, (ii) decreased total JNK and phospho‐p54 JNK and (iii) p21WAF1 down‐regulation. Altered JNK activation and p21WAF1 down‐regulation were accompanied by defects in maintaining G2/M and mitotic spindle checkpoints through adaptation, as well as by apoptosis resistance following H2O2 exposure. This may cause increased proliferation of C‐cell cultures, a defining initiating feature in the inflammation‐carcinoma pathway in UC. We further suggest that dysregulated JNK activation is attributed to a non‐apoptotic function of caspases, causing checkpoint adaptation in C‐cell cultures. Additionally, loss of cell‐contact inhibition and the overcoming of senescence, hallmarks of cancer, contributed to increased proliferation. Furthermore, there was evidence that p54 JNK inactivation is responsible for loss of cell‐contact inhibition. We present a cellular model of UC and suggest a sinusoidal pattern of proliferation, which is triggered by H2O2‐induced reactive oxygen species generation, involving an interplay between JNK activation/inactivation, p21WAF1, c‐Fos, c‐Jun/phospho‐c‐Jun, ATF2/phospho‐ATF2, β‐catenin/TCF4‐signalling, c‐Myc, CDK6 and Cyclin D2, leading to driven cell cycle progression.